ISO 9126 Untuk Pengujian Kualitas Aplikasi Perpustakaan Senayan Library Management System (SLiMS) - Petrus Dwi Ananto Pamungkas (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The rapid development of information systems has made changes almost in all areas of human activity, including the management of college libraries. The presence of reliable software (application) library Senayan Library Management System (SLiMS), it is very helpful to the person in charge of college library in managing the library, e.g: inputing the data, searching, borrowing and returning the library collection. The large number of usage of SLiMS application is expected not only because of its Open Source Software or free usage and license but also because of its good application quality. Using the Functionality, Reliability, Usability, Efficiency, Maintainability and Portability aspects of ISO 9126 standards, it is possible to test the quality of SLiMS application. The data collection method used is Google Forms in creating and distributing questionnaire and interview to some of the person in charge of college library. The result of data collection is processed to obtain information that SLiMS application classified as VERY GOOD category. It means that SLiMS application which has been used by some of the person in charge of college library, obviously it has excellent quality and very helpful in the management of college libraries.